Polymer grafting and crosslinking - Bhattacharya, Amit; Rawlins, James Wayne; Ray, Paramita (John Wiley, 2009)
"Following this book's step-by-step explanations, readers discover how to take advantage of polymer grafting and crosslinking to modify polymer materials in order to make them suitable for specific applications. Moreover, the authors demonstrate how this can be achieved economically and without the need for developing brand-new materials." "While much information has been published in the area of polymer grafting and cross-linking, it has been spread across a broad range of journals and references. This single volume brings together in one place the core science, methodologies, and applications, making it an ideal practical manual for polymer chemists, surface chemists and physicists, and membrane scientists."--BOOK JACKET.